Analysis of the Effect of Socioeconomic Factors on Poverty in Central Java Province - Khaqiqi, Moh. Nur; Sugiharti, Lilik (Universitas Airlangga, 2025)
Central Java, despite experiencing robust economic growth, continues to grapple with significant poverty, reflecting a broader national challenge of uneven wealth distribution. The poverty rate as of 2023 stands at 10.77%, highlighting persistent economic disparities. The study aims to analyze how socioeconomic factors like economic growth, HDI, and wage levels contribute to poverty alleviation within the region. The research uses a quantitative approach, employing regression random effect models to understand the dynamics between these variables and poverty rates over the years 2014-2023. Data were processed using Stata 17. The analysis indicates that economic growth in Central Java has an insignificant direct impact on reducing poverty. The research highlights a significant negative correlation between HDI and poverty levels. This study found that wage increases have not significantly impacted poverty reduction. Simultaneously, GDRP growth, HDI, and wages affect poverty in Central Java province. The findings suggest that merely focusing on economic growth and wage increases is not enough to reduce poverty. Comprehensive strategies that also improve human development indices and address income distribution are crucial for effective poverty alleviation.